The human body how we fail, how we heal - Goodman, Anthony A.; Teaching Company (Chantilly, Va. : Teaching Co., 2007)
In this video course, Dr. Anthony Goodman presents a systematic survey of what can go wrong in the human body, why it goes wrong and how the body itself responds, as well as what doctors can do to intervene.
Part 2. Lecture 13. Malaria -- lecture 14. Schistosomiasis, Filariasis, tapeworms -- lecture 15. Infectious diseases--treatment -- lecture 16. Infectious diseases--triumph and failure -- lecture 17. Shock--principles and hypovolemic shock -- lecture 18. Categories of shock -- lecture 19. Cancer--the enemy within -- lecture 20. Environmental carcinogens -- lecture 21. Mechanisms of carcinogenesis -- lecture 22. Invasion, metastasis, and angiogenesis -- lecture 23. Treatment--surgery, radiation, chemotherapy -- lecture 24. How we heal.
"Course no. 1564."
Twenty-four lectures (30 min. each).
Two part set in two containers.
Lectures by Anthony A. Goodman, Adjunct Professor of medicine at Montana State University.
DVD.
Keywords: Human physiology; Diseases -- Causes and theories of causation; Physiology, Pathological